Adaptive Control of a Non-Cylindrical Tank - Nippert, Charles; Coburn, Rebecca; Shea, Brendan; Roth, Michael; Harrell, Clinton; Owusu, Edward (International Journal of Online and Biomedical Engineering (iJOE), 2013)
A conical tank in which the diameter changes with the tank height, allows the use of feedback control used in complex nonlinear systems, such as adaptive control. This project modified an existing system of two interacting tanks by inserting a removable solid cone into one of the tanks. This modification created two new nonlinear configurations, one of which had a discontinuity. Optimal controller settings at different depths of liquid were found by minimizing the integral of the absolute error (IAE). These settings were used by an adaptive PID controller at a different settings, comparing the results to a conventional PID tuned to that setting.